The Grammars of Seem - Thrane, Torben (HERMES - Journal of Language and Communication in Business, 2017)
This paper is the ms. of my inaugural lecture at the Aarhus School of Business, 26th September, 1995, with minor modifications. It traces some of the basic assumptions of Chomskyan theories of syntax, as they have determined the requirements of a syntactic description of English sentences containing the verb seem at various points in time. It is shown that although the purpose of linguistic description must be taken into account when choosing between competing, descriptively adequate grammars, this will not be enough unless the goal of linguistic explanation is accessible to independent investiga-tion. It is argued that a reformulation of the issue between functional explanation or not in linguistics may overcome the problem.